2019
DOI: 10.1210/js.2019-or14-5
|View full text |Cite
|
Sign up to set email alerts
|

OR14-5 Challenges in implementing Hybrid Closed Loop Insulin Pump Therapy (medtronic 670g) In A 'Real World' Clinical Setting.

Abstract: An observation study was conducted at Boston Children’s Hospital on patients with type 1 diabetes mellitus (T1DM) who elected to treat their diabetes with the FDA approved Medtronic 670G hybrid closed loop insulin pump. 83 pediatric and young adults were trained and started on the Medtronic 670G in automode between 5/30/17-9/7/18 (Age range 6-25 years). Average follow up time for the patient population was 8 months (range 3-18 months). 19% (16/83) of T1DM patients discontinued use of automode hybrid closed loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
1
16
1
1
Order By: Relevance
“…There is substantial evidence that HCL systems have potential to improve overall glycemic control, with many controlled trials reporting increased time in target range and reduction in hyperglycemia and hypoglycemia . However, individuals need to use HCL consistently to realize these benefits, and emerging observational data of 670G HCL use in the real‐world suggests a high risk for HCL discontinuation as well as attrition in time spent in HCL for those who continue using it…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial evidence that HCL systems have potential to improve overall glycemic control, with many controlled trials reporting increased time in target range and reduction in hyperglycemia and hypoglycemia . However, individuals need to use HCL consistently to realize these benefits, and emerging observational data of 670G HCL use in the real‐world suggests a high risk for HCL discontinuation as well as attrition in time spent in HCL for those who continue using it…”
Section: Discussionmentioning
confidence: 99%
“…Data from our group's observational study presented elsewhere indicate that Auto Mode use and sensor wear decreased over the first 6 mo of use, and 30% of the youth discontinued HCL altogether . In addition, other prospective observational studies have reported 35% and 38% of patients discontinuing Auto Mode use in the first 9‐12 mo of system use . The reasons for HCL discontinuation are not well documented, with one report indicating sensor issues and difficulty obtaining supplies as primary reasons .…”
Section: Introductionmentioning
confidence: 99%
“…Cited reasons for discontinuation included calibration requirements, problems with sensor durability or adhesion, skin irritation and forced exits from Auto Mode . The percentage time spent in Auto Mode was also highly variable, ranging from 10% to 90% . Although the percentage of time in Auto Mode was comparatively higher in the pivotal 670G trial, Auto Mode time declined from a peak of 87% after the first 7 days of use to 72% at the 3‐month endpoint in the adolescent and young adult subanalysis .…”
Section: Discussionmentioning
confidence: 99%
“…7 Cited reasons for discontinuation included calibration requirements, problems with sensor durability or adhesion, skin irritation and forced exits from Auto Mode. 7 The percentage time spent in Auto Mode was also highly variable, ranging from 10% to 90%. 7 Although the percentage of time in Measures of dietary intake were also significant covariates in the multivariable regression models.…”
Section: Additional Bivariate Analyses Of Variables Of Interest Are Dmentioning
confidence: 99%
See 1 more Smart Citation